DASAR biologis dan klinis peyakit infeksi Stanfoed T. Shulman, John P. Phair, Herbert M. Sammers; penerjemah A. Samik Wahab ; penyunting Sutarjo - Sutarjo; Wahab, A. Samik; Sammers, Herbert M.; Phair, John P.; Shulman, Stanford T. (1994)
xii, 673 hlm. ilus. 28 cm.